2015
DOI: 10.1111/1750-3841.13092
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Herbal Tea Leaves from Yacon (Smallanthus sonchifolius) on Multiple Free Radical and Reducing Power Assays, Especially on Different Superoxide Anion Radical Generation Systems

Abstract: Yacon has been considered to be a potent alternative food source for patients who require a dietary cure in regional area, while the leaf part has been provided and consumed as an herbal tea in local markets. We demonstrated here potent antioxidative effects of the tea leaves from yacon in different free radical assays, reducing power assay, and cellular superoxide anion radical generation assay. Results support yacon tea leaves may be a good source of natural antioxidants for preventing O2(-) radical-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 64 publications
(96 reference statements)
0
24
0
4
Order By: Relevance
“…Furthermore, as phenolic acid and flavonoid compounds may contribute to ABTS radical scavenging activity of yacon leaves, the higher amount of ABTS radical scavenging activity obtained in the present study is in agreement with higher amounts of TFC and TPC extracted compared to findings of De Andrade et al [ 9 ]. ABTS radical scavenging activity of aqueous extracts of yacon leaves has been also studied using EC 50 methodology in study of Sugahara et al which cannot be compared to the results of present study due to differences in analytical methods [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as phenolic acid and flavonoid compounds may contribute to ABTS radical scavenging activity of yacon leaves, the higher amount of ABTS radical scavenging activity obtained in the present study is in agreement with higher amounts of TFC and TPC extracted compared to findings of De Andrade et al [ 9 ]. ABTS radical scavenging activity of aqueous extracts of yacon leaves has been also studied using EC 50 methodology in study of Sugahara et al which cannot be compared to the results of present study due to differences in analytical methods [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there was a week positive correlation between DPPH radical scavenging activity and TFC ( R = 0.350, Table 5 ). DPPH radical scavenging activity of yacon leaves extract was studied according to EC 50 methodology by other researches [ 9 , 36 ]. Due to differences in analytical methods applied in these investigations and the present study, the results cannot be compared.…”
Section: Resultsmentioning
confidence: 99%
“…There was a linearity of absorbance versus concentrations with a coefficient of determination R 2 of 0.997 and 0.999 for AA and PP extract, respectively. The concentration giving the arbitrary absorbance 0.5 was assumed to be the IC 50 (Sugahara et al, ). The value of IC 50 showed that PP extract is twice higher antioxidant comparing to AA (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Reducing power with absorbance 1.0 is equal to100% of reductivity. The effective concentration obtaining 0.5 of absorbance or 50% reductivity, is assumed to be EC50 (”g/mL) (Sugahara et al, 2015).…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%